Writers of the Winter Republic : Literature and Resistance in Park Chung Hee's Korea - Ryu, Youngju (Book collections on Project MUSE., 2015)
In 1975, a young high school teacher took the stage at a prayer meeting in a southwestern Korean city to recite a poem called "The Winter Republic." The poem became an anthem against the military dictatorship of Park Chung Hee and his successors; the poet, however, soon found himself in court and then in prison for saddling the authoritarian state with such a memorable moniker. This unique book weaves together literary works, biographical accounts, institutional histories, trial transcripts, and personal interviews to tell the powerful story of how literature became a fierce battleground against authoritarian rule during one of the darkest periods in South Korea's history. Park Chung Hee's military dictatorship was a time of unparalleled political oppression. It was also a time of rapid and unprecedented economic development. Against this backdrop, Youngju Ryu charts the growing activism of Korean writers who interpreted literature's traditional autonomy as a clarion call to action, an imperative to intervene politically in the name of art. Each of the book's four chapters is devoted to a single writer and organized around a trope central to his work. Kim Chi-ha's "bandits," satirizing Park's dictatorship; Yi Mun-gu's "neighbor," evoking old nostalgia and new anxieties; Cho Se-hŭi's dwarf, representing the plight of the urban poor; and Hwang Sok-yong's labor fiction, the supposed herald of the proletarian revolution. Ending nearly two decades of an implicit ban on socially engaged writing, literature of the period became politicized not merely in content and form, but also as an institution. Writers of the Winter Republic emerged as the conscience of their troubled yet formative times. A question of politics lies at the heart of this book, which seeks to understand how and why a time of political oppression and censorship simultaneously expanded the practice and everyday relevance of literature. By animating the lives and works of the men who shaped this period, the book offers readers an illuminating literary, cultural, and political history of the era